2018
DOI: 10.1371/journal.pone.0208921
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bone osteometry, mineralization, mechanical and histomorphometrical properties of tibiotarsus in broiler chickens demonstrates a influence of dietary chickpea seeds (Cicer arietinum L.) inclusion as a primary protein source

Abstract: This study was focused on analyzing the effects of dietary inclusion of raw chickpea seed as a replacement of soybean meal as a primary protein source on bone structure in broiler chickens. Broiler chickens (n = 160) received in their diet either soybean meal (SBM) or raw chickpea seeds (CPS) as a primary protein source throughout the whole rearing period (n = 80 in each group). On the 42th day randomly selected chickens from each group (n = 8) were slaughtered. Collected tibiotarsus were subjected to examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 58 publications
2
36
0
1
Order By: Relevance
“…The dietary inclusion of CPS influenced the mechanical properties of tendons and thermal stability of tendon collagen proteins in broiler chickens (Muszyński et al, 2018a). On the other hand, there was no effect of CPS inclusion on thermal properties of collagen structures of the articular cartilage of the tibia (Muszyński et al, 2018b).…”
Section: Introductionmentioning
confidence: 95%
“…The dietary inclusion of CPS influenced the mechanical properties of tendons and thermal stability of tendon collagen proteins in broiler chickens (Muszyński et al, 2018a). On the other hand, there was no effect of CPS inclusion on thermal properties of collagen structures of the articular cartilage of the tibia (Muszyński et al, 2018b).…”
Section: Introductionmentioning
confidence: 95%
“…Despite this, we prepared our mixtures to be also isonitrogenous and isoenergetic. However, as presented in previous works, despite the fact that experimental diets were not adjusted to other nutrients, the diet type did not have a significant effect on chicken weights (2320 ± 125 g and 2404 ± 170 g for the SBM and CPS group, respectively; p = 0.279) or feed conversion ratio (1.93 ± 0.34 kg/kg and 1.88 ± 0.44 kg/kg, for the SBM and the CPS groups, respectively; p = 0.863) [12,13]. A very recent experiment also showed that inclusion of raw CPS through the whole rearing period does not influence body weight gain and feed conversion ratio in turkeys [37].…”
Section: Resultsmentioning
confidence: 98%
“…The diets were isonitrogenous, isoprotein, and isoenergetic ( Table 1). Bird management and care are described in detail in previous works [12,13]. Individual body weight and feed intake (per pen) were monitored.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations